Potential Analysis of Brown Sugar Industry Liquid Waste as Raw Material on Making Nata de Coco - Gunawan Wijonarko; Ike Sitoresmi Mulyo Purbowati; Ali Maksum (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2023)
Brown sugar industry liquid waste is a type of waste that has potential as a medium for making nata. This is because coconut sugar industry liquid waste still contains a lot of sugar as a source of nutrition for the growth of Acetobacter xylinum. In this study, a comparative analysis will be carried out to determine the feasibility of brown sugar industry liquid waste as a medium for making nata. The research was conducted for 2 months at UKM Ngudi Lestari Jaya, Kalisalak Village. Samples were taken randomly using sterile plastic bottles. Sample analysis includes viscosity, color, aroma, degree of brix and pH. Observations on viscosity, color and aroma were carried out before and after boiling. Variable measurements were carried out 3 times. The sensory properties of the samples were analyzed by descriptive qualitative. Brix degree and pH value were analyzed using SPSS version 2.1 with the independent t test method at an alpha value of 5%. The sensory and chemical properties of brown sugar industry liquid waste were compared with coconut water as a standard. The results showed that the liquid waste from the brown sugar industry had a dilute to slightly thick viscosity, light brown to brown color and normal aroma. The results of a comparative analysis showed that there was no difference in sensory properties between the liquid waste and coconut water before and after boiling. The brix degree and the pH value of brown sugar industry liquid waste were respectively 4.3% and 6.3. Meanwhile, the degree of brix and the pH value of coconut water were 5.1% and 5.6, respectively. Based on this, it can be concluded that the liquid waste of brown sugar industry has very good potential as a medium for making nata.